A corpus‐driven, curriculum‐based Chinese elicited imitation test in US universities. (12th January 2021) - Yan, Xun; Lei, Yuyun; Shih, Chilin
Abstract: This two‐phased study explored a corpus‐driven, curriculum‐based approach to assessing proficiency development of Mandarin Chinese in US universities. In Phase I, we developed an elicited imitation (EI) test based on the Chinese curriculum at a large US university. This test demonstrated higher psychometric qualities to (1) place L2 learners into three curricular levels, and (2) assess learners' production of key vocabulary and grammatical items, providing useful information for placement, diagnosis, and achievement purposes as compared with a non‐curriculum‐based EI test. In Phase II, we revised the EI test to make it applicable across university contexts. We identified a lexico‐grammar core from a corpus‐driven analysis of 36 widely‐used Chinese textbooks in US universities and incorporated this core in EI item development. The revised EI test showed improved psychometric qualities. This study has broad methodological implications for the assessment of Chinese as well as other less commonly taught languages in university contexts. The Challenge: There is an increasing number of general language proficiency tests available for teachers and program administrators in less commonly taught languages programs. However, are these tests well linked to the language curriculum in your context? How useful are they for placement, diagnosis, and achievement purposes? This article presents a corpus‐driven, curriculum‐based approach to assessing proficiency development of Mandarin Chinese, a less commonly taught language (LCTL) in US universities. The full version of the test is provided, and the methodological implications of the corpus‐driven, curriculum‐based approach for the assessment of Chinese as well as other LCTLs are also discussed.